CuZn40Pb2 ALLOY PLATE FINE BLANKING HOLE WALL QUALITY PREDICTION BASED ON ANALYSIS OF DAMAGE AND MICROSTRUCTURE - LI Feng; FAN WenJie; YUE Yun (Jixie qiangdu)
In order to provide a better evaluation basis to optimize blanking process,a blanking hole wall surface quality predict method was proposed,the method used DAMAGE figure maximum damage value to predict the quality. Taking CuZn40Pb2 alloy plate as research object,the positive and negative clearance blanking models were established. By analyzing each node displacement changes,damages and blanking forces,two kinds of blanking simulation results show that the positive and negative clearance blanking hole damages main reasons are: tensile tear and crush damage. According to the simulation of the micro-structure changes in two blanking processes,the blanking hole wall with positive and negative clearance damage extent and position distribution are obtained. The flaw probabilities on the fine blanking hole wall in the positive clearance was calculated to be 2. 96 times that of the negative clearance blanking. After the blanking test,the microstructure changes at the positive and negative clearance blanking observed under the light microscope was consistent with the prediction result. The quantification of the maximum value of damage by the DAMAGE figure can predict the wall surface quality of blanking holes,the punching process can be selected according to the maximum value of damage by the DAMAGE figure.